Single carrier PWM scheme for cascaded multilevel voltage source inverter - Zainal, S.; Aziz, J.; Ahmed, S. S. (2003)

(untitled)
This work proposes a new switching scheme for the cascaded multilevel inverter. Unlike other schemes, the proposed method is based on the symmetric regular sampling PWM with a single carrier and multiple modulating signals. Non-transcendental trigonometric equations that define the switching instants of the multilevel inverter are derived. This algorithm is implemented by a low-cost fixed-point microcontroller on an experimental five level cascaded inverter test-rig.